Comparative microscopic analysis of nail clippings from patients with cutaneous psoriasis and psoriatic arthritis - Gabriela Poglia Fonseca; Betina Werner; Gabriela Seidel; Henrique Luiz Staub (Sociedade Brasileira de Dermatologia, 2017)
Abstract: BACKGROUND: The nail involvement in psoriasis is related to psoriatic arthritis and may represent a predictor of the disease. OBJECTIVES: To analyze, through nail clipping, clinically normal and dystrophic nails of patients with cutaneous psoriasis and psoriatic arthritis. METHODS: This is a cross-sectional multicenter study, conducted between August 2011 and March 2012. Patients were divided into four groups: patients with cutaneous psoriasis and onychodystrophy, patients with cutaneous psoriasis and clinically normal nails, patients with psoriatic arthritis and onychodystrophy and patients with psoriatic arthritis and clinically normal nails. We calculated NAPSI (Nail Psoriasis Severity Index) of the nail with more clinically noticeable change. After collection and preparation of the nail clipping, the following microscopic parameters were evaluated: thickness of the nail plate and subungual region, presence or absence of parakeratosis, serous lakes, blood, and fungi. RESULTS: There were more layers of parakeratosis (p=0.001) and a greater thickness of the subungual region in patients with cutaneous psoriasis and onychodystrophy (p=0.002). Serous lakes were also more present in the same group (p=0.008) and in patients with psoriatic arthritis and normal nails (p=0.047). The other microscopic parameters showed no significant difference between normal and dystrophic nails or between patients with psoriatic arthritis or cutaneous psoriasis. STUDY LIMITATIONS: Small sample size and use of medications. CONCLUSIONS: Nail clipping is a simple and quick method to assess the nails of patients with nail psoriasis although does not demonstrate difference between those with joint changes or exclusively cutaneous psoriasis.